Elephantine Judaism / Yahwism in the context of Elephantine during the Achaemenid Period - Stökl, Jonathan (NTT, 2025)
This paper explores the religious identity and practices of the Jewish community in Elephantine during the Achaemenid period, focusing on the archaeological and textual evidence from the site itself, rather than the Hebrew Bible. It critiques previous scholarship’s reliance on biblical texts to interpret Elephantine Judaism, which often viewed it as either a deviation or a purer form of biblical Judaism. The study emphasizes a need for a fresh approach that considers Elephantine’s own cultural context and artifacts, highlighting the diversity of religious practices, including syncretic elements and unique customs, as distinct expressions of Elephantine’s community identity.